2009
DOI: 10.1371/journal.pone.0005438
|View full text |Cite
|
Sign up to set email alerts
|

Lef1 Haploinsufficient Mice Display a Low Turnover and Low Bone Mass Phenotype in a Gender- and Age-Specific Manner

Abstract: We investigated the role of Lef1, one of the four transcription factors that transmit Wnt signaling to the genome, in the regulation of bone mass. Microcomputed tomographic analysis of 13- and 17-week-old mice revealed significantly reduced trabecular bone mass in Lef1+/− females compared to littermate wild-type females. This was attributable to decreased osteoblast activity and bone formation as indicated by histomorphometric analysis of bone remodeling. In contrast to females, bone mass was unaffected by Lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 69 publications
2
58
0
Order By: Relevance
“…Thus, increased PGE 2 synthesis may contribute to activation of PI3K/Akt/GSK-3/␤-catenin signaling in shearstressed osteoblasts and osteocytes, especially at later time points. The skeletal phenotypes of mice with genetic alterations in the PI3K/Akt/GSK-3 pathway confirm the importance of this pathway for regulating bone formation and stimulating osteoblast differentiation (58,60,61).…”
Section: Discussionmentioning
confidence: 64%
“…Thus, increased PGE 2 synthesis may contribute to activation of PI3K/Akt/GSK-3/␤-catenin signaling in shearstressed osteoblasts and osteocytes, especially at later time points. The skeletal phenotypes of mice with genetic alterations in the PI3K/Akt/GSK-3 pathway confirm the importance of this pathway for regulating bone formation and stimulating osteoblast differentiation (58,60,61).…”
Section: Discussionmentioning
confidence: 64%
“…Gender-specific enhanced sensitivity of female mice toward modulation of Wnt/␤-catenin signaling was also reported for other loss-offunction mutants of Wnt/␤-catenin signaling components (37,50,72). Whether these observations are due to cross talk of Wnt/␤-catenin and sex steroid signaling pathways or related to sexually dimorphic bone mass accrual, bone turnover, and/or osteocyte mechanotransduction (3,41,59,72) is currently unknown and remains to be addressed by future studies.…”
Section: Vol 30 2010mentioning
confidence: 72%
“…The Impact of Bone-specific Progerin Expression on DNA Damage Response-To test for changes in Wnt signaling, which has previously been seen in HGPS, we found that the lymphoid enhancer-binding factor (Lef1), which is a Wnt-regulated transcription factor known to regulate osteoblast maturation (35), was significantly reduced in our mouse model. Furthermore, when HGPS mice were compared with wild-type animals, we saw an overall trend toward the lower expression for most of the studied target genes, including Cdkn1a, Jag1, Jag2, Hes1, and Tcf3 (Fig.…”
Section: The Transactivator Regulates the Transgenic Expression-mentioning
confidence: 73%